INTEGRATING THE PRINCIPLES OF SUSTAINABLE DEVELOPMENT INTO CORPORATE GOVERNANCE: GUIDELINES AND CHALLENGES - Luchkov Кiril (E-Journal VFU, 2025)
This study explores how sustainable development principles can be integrated into corporate governance to achieve long-term competitiveness and social responsibility. It looks at the main ways to include sustainable practices in business strategies and management, as well as the challenges companies face during this process. The study highlights the need for a comprehensive approach that includes economic, social, and environmental factors, encourages innovation, improves corporate reputation, and supports sustainable growth. Recommendations are given to overcome the main barriers to integrating sustainability into management processes.